Toward a food secure future: Ensuring food security for sustainable human development in Sub-Saharan Africa. (April 2016) - Conceição, Pedro; Levine, Sebastian; Lipton, Michael; Warren-Rodríguez, Alex
Highlights: Food security is a core component of the human development and capability paradigm. Agriculture is central to improving food security and reducing poverty in Africa. Realizing the potential of agriculture in Africa requires rapid increases in yields. A science-based approach that integrates gender and sustainability can achieve this. Abstract: Food security remains a top development priority and global concern. It is enshrined in the 2030 Agenda for Sustainable Development in Sustainable Development Goal two. Food security is also a core component of the human development and capability paradigm, since food access and entitlements are critical for reinforcing essential human capabilities. In introducing this special issue, this paper argues that agriculture is central to improving food security and reducing poverty in Africa. It suggests that realizing the potential of agriculture in Africa requires rapid increases in land productivity and increases in agricultural yields. A science-based approach that integrates gender and sustainability is critical to meet this goal, through the design and implementation of policies that improve the availability farm inputs and farm technology. The paper concludes by introducing the papers in this special issue.